Effect of Milk thistle (Silybum marianum L.) and Thyme (Thymus vulgaris L.) herbs on immunity and some blood metabolites in broiler chicks - omid fanimakki; ahmad ebrahimzade; hossein ansarinik; mahmoud ghazaghi (Āsīb/shināsī-i Darmāngāhī-i Dāmpizishkī, 2013)
This experiment was conducted to evaluate the ability of two herbs (Thyme and Milk thistle seed) on immunity and some blood metabolites in broiler chickens. In this study, 160 one-day-old Ross 308 broiler chicks were used. They were randomly assigned to four treatments, with 4 replicates and 10 birds in each unit. The birds were reared on litter for 21 days. Group T1 was kept as a control, the other treatments received feed containing milk thistle and thyme seeds for 3 weeks, i.e. (T2) Milk thistle seed (200 mg kg-1); (T3) Thyme seed (200 mg kg-1); (T4) a combination of thistle and thyme seed added to the basal diet (200 + 200 mg kg-1). There were no significant differences in IgA, IgG, IgM, liver enzymes activity (AST, ALT and GGT), HI titer values against Newcastle, Influenza, Bronchitis and Gambru disease virus in broilers fed different levels of herbs after challenge with (sheep red blood cells-sRBCs) (8 Percent). The results showed that with combination of milk thistle and thyme seeds in poultry diets, some variables in serum (total protein, globulin, albumin and HDL) were increased and cholesterol, LDL and triglyceride were decreased compared to control group (P < 0.05). In addition, the lymphocyte and heterophil counts, were increased in birds fed a combination of diets (P < 0.05). In conclusion, use of thyme and milk thistle seeds, and particularly their combination had improved some blood metabolites and decreased harmful fatty acids in blood of broiler chicks.